The alcoholism and addiction cure - Prentiss, Chris, 1936- (Los Angeles, Calif. : Power Press, 2007)
Contains the three-step holistic program to total recovery that is the basis of the successful Passages approach. You will learn: the three steps to permanent sobriety; how to create a personalized, holistic treatment program to completely cure your dependency; the four causes of dependency; how your thoughts, emotions, and beliefs are key factors in your recovery; and how to stimulate your body's self-healing potential to be forever free of dependency.--From publisher description.
Includes bibliographical references (p. 329-331) and index.
Keywords: Alcoholism; Alcoholism -- Treatment; Alcoholism -- Diet therapy